Effect of cryopreserved fragments of piglet‘s skin extract or aqueous colloidal solution of fullerene c60 on wound healing after skin cryoablation - Vlasov., O.O.; Kovalov, G.O.; Halchenko, S.Ye.; Чиж, М.О. (The 1st International scientific and practical conference – Modern science: problems and innovations (April 5-7, 2020) SSPG Publish, Stockholm, Sweden. 84–87., 2020)
Effect of cryopreserved fragments of piglet‘s skin extract or aqueous colloidal solution of fullerene C60 on wound healing after skin cryoablation
Vlasov O., Kovalov G., Halchenko S., Chyzh M. Effect of cryopreserved fragments of piglet‘s skin extract or aqueous colloidal solution of fullerene C60 on wound healing after skin cryoablation (2020) The 1st International scientific and practical conference – Modern science: problems and innovations (April 5-7, 2020) SSPG Publish, Stockholm, Sweden. 84–87.
Keywords: cryopreserved fragments of piglet‘s skin extract; colloidal solution of fullerene C60; skin cryoablation